2014
DOI: 10.1387/ijdb.140308ho
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular localizations of the Dead End protein in Xenopus primordial germ cells

Abstract: We investigated the intracellular localization of Xenopus Dead end protein (Dnd1) in primordial germ cells during early development by expressing the tagged protein in transgenic Xenopus embryos, with the germ plasm visualized. Dnd1 initially localized to the germ plasm in the cortex, moved to the perinuclear region together with the germ plasm after the midblastula transition, and then entered the nucleus. Using Dnd1 deletion mutants, we identified two distinct but overlapping regions of Dnd1 that were respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For Dnd1, the deduced amino acid sequence of the Dnd1 protein contained the typical RRM and five conserved regions (NR, CR1–4). The RRM is known as the RNA-binding domain necessary for the regulation of protein localization in germ cells [ 13 , 45 , 46 , 47 , 48 , 49 ]. Phylogenetic analysis demonstrated that Dnd clustered with the Dnd families of teleosts.…”
Section: Discussionmentioning
confidence: 99%
“…For Dnd1, the deduced amino acid sequence of the Dnd1 protein contained the typical RRM and five conserved regions (NR, CR1–4). The RRM is known as the RNA-binding domain necessary for the regulation of protein localization in germ cells [ 13 , 45 , 46 , 47 , 48 , 49 ]. Phylogenetic analysis demonstrated that Dnd clustered with the Dnd families of teleosts.…”
Section: Discussionmentioning
confidence: 99%
“…DND1 has been detected in both the cytoplasm and nucleus [37][38][39], in line with the function of DND1 as a post-transcriptional [7,9,10,29] or transcriptional regulator [36]. What determines the multifaceted regulatory roles of DND1 is still unknown.…”
Section: Other Molecular Functions Of Dnd1mentioning
confidence: 91%
“…In the fertilized embryo, Dnd moves from the cortex to the perinuclear region with germplasm and enters the nucleus. It is speculated that Dnd carries RNA into the nucleus to trigger germline specification (Taguchi et al, 2014).…”
Section: Localisationmentioning
confidence: 99%